EFFECTIVENESS OF HYPOTHERMIC THERAPY IN PATIENTS STOP HEART POST: LITERATURE REVIEW - Mardiana, Mardiana; Mas'ud, Alfian (Jurnal Keperawatan Respati Yogyakarta, 2021)
Cardiac arrest has become one of the most unexpected, dramatic, and life-threatening events in the world of health. The increase in the number of patients who survived after cardiac pulmonary resuscitation has increased as more cardiopulmonary resuscitation training and defibrillation equipment are becoming easier to carry to various locations, but brain damage begins within minutes of cardiac arrest with the consequence of patients having their hearts beating again. and hospitalized unable to leave the hospital or in a vegetative state. Hypothermic therapy has been used frequently in cardiac surgery for several years for neurological protection. The data-based used in making this literature review are Google Scholar and Proquest. The keywords used in the search for articles on google scholar are "Therapeutic" and "Hypothermia" and "post" and "cardiac" and "arrest" and limit the publication year of 2011-2016. While the search on Proquest "Therapeutic" and "Hypothermia" and "after" and "cardiac" and "arrest". Based on the results of the literature search on google scholar, there were 9730, Pubmed 150, and ProQuest 2460. The screening results were 7,200 but only 9 journals were relevant to the topic. Hypothermic therapy can significantly improve neurological status in post-cardiac arrest patients even after the patient has been discharged from the hospital Keywords:Hypothermic Therapy; Post Cardiac Arrest